2013
DOI: 10.1371/journal.pgen.1003976
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Ablation of Crb1 and Crb2 in Retinal Progenitor Cells Mimics Leber Congenital Amaurosis

Abstract: Development in the central nervous system is highly dependent on the regulation of the switch from progenitor cell proliferation to differentiation, but the molecular and cellular events controlling this process remain poorly understood. Here, we report that ablation of Crb1 and Crb2 genes results in severe impairment of retinal function, abnormal lamination and thickening of the retina mimicking human Leber congenital amaurosis due to loss of CRB1 function. We show that the levels of CRB1 and CRB2 proteins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 46 publications
5
97
0
2
Order By: Relevance
“…However, in contrast with the observation made in the Crb2Chx10 cKO (11,13), in the Crb2Crx cKO the lamination of ganglion, amacrine, bipolar and Müller glial cells was also affected, misplaced inner retinal cells were detected ectopically in the ONL. Similar defects in the lamination of these cells were also observed in CRB2 null retinas with half of the amount of CRB1 (Crb1 +/2 Crb2Chx10 cKO) (17). These results are in line with (i) previous zebrafish data where Crb2a is required for retinal cell patterning and lamination (30) and (ii) mouse data where the CRB-interacting protein PALS1 affected the correct patterning of photoreceptor cells (31,32).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, in contrast with the observation made in the Crb2Chx10 cKO (11,13), in the Crb2Crx cKO the lamination of ganglion, amacrine, bipolar and Müller glial cells was also affected, misplaced inner retinal cells were detected ectopically in the ONL. Similar defects in the lamination of these cells were also observed in CRB2 null retinas with half of the amount of CRB1 (Crb1 +/2 Crb2Chx10 cKO) (17). These results are in line with (i) previous zebrafish data where Crb2a is required for retinal cell patterning and lamination (30) and (ii) mouse data where the CRB-interacting protein PALS1 affected the correct patterning of photoreceptor cells (31,32).…”
Section: Discussionsupporting
confidence: 89%
“…We hypothesize that CRB1 in Müller glial cells (14,34) compensated in Crb2Pdgfra cKO retinas for the loss of CRB2. We recently demonstrated that removal of CRB1 in a CRB2 null retina exacerbate the CRB2 phenotype in a dosedependent manner (17). Thus, mouse retinas with complete depletion of CRB1 and CRB2 from Müller glial cells could answer this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retinal laminar structure on SD OCT in our patient cohort was relatively intact compared with that of earlier studies that described coarse lamination, defined as unclearly delineated retinal layers, in mice and patients with CRB1-associated retinal dystrophies, in both thickened and atrophic areas of retina. 3,12,13,34 Although our findings suggest progressive over congenital changes, a limitation of this study is the lack of longitudinal OCT follow-up, which could clarify if such coarse OCT lamination is the result of a congenital or a degenerative process. The finding of peripheral loss of delineation with central islands of intact lamination in an RP phenotype with centripetal progression would support the notion of intact retinal lamination at birth followed by progressive retinal dystrophy with consequent loss of outer retinal lamination in the affected areas.…”
Section: Discussionmentioning
confidence: 70%
“…Gross morphological defects are preceded by problems in the integrity of the zonula adherens (ZA; the outer limiting membrane of the vertebrate retina) that emerge during terminal differentiation of the retina, and a failure to form inner and/or outer segments of normal size. Crb1 Crb2 double mutants show more severe defects than Crb1 mutants and resemble human patients with Leber congenital amaurosis (Pellissier et al, 2013), suggesting that Crb2 also plays an important role in retinal development. Numerous disease-causing mutations in CRB1 have been reported in human patients ( Fig.…”
Section: Introductionmentioning
confidence: 99%